A Feasibility Study on Premium Diesel, Inc. - Baterina, Eunessa A.; De Leon, Salve I.; Entico, Maria Cecilia E. (Diliman, Quezon City College of Engineering, 2003)
The Philippine Coconut Authority, in its advance towards maximizing the potential of one of the most abundant resources in the country?coconut and as inspired by the government?s policy?the Clean Air Act, developed coconut diesel as an alternative fuel. This is a blend of diesel and coconut methyl ester?special oil derived from the coconut. Studies have shown that use of coconut diesel in public utility vehicle results in smoother combustion and increased mileage. But most importantly, coconut diesel reduces smoke emission by up to 50% thus helping in reduction, if not elimination, of air pollution. However, no mixing plant exists yet to produce the product for commercial use. Hence, a feasibility study was conducted to determine if taking the project is worth the time, money and effort of the government and potential financing institutions., if intended to determine the credibility of the very first manufacturing plant of coconut diesel, which will also house Premium diesel, Inc. the company that aims to offer the best diesel fuel?coconut diesel to the country. The marketing study determined which market is to target and how to develop market strategies that would ensure positioning of coconut diesel in the oil industry. The survey conducted showed willingness of consumers to buy; hence, there is potential marketability of the product, especially for public utility vehicles situated in the National Capital Region. The demand for coconut diesel was determined using the moving average forecasting method based on the gathered previous years demand considering the efficiency it will provide. In five years, Premium Diesel, Inc. expects to increase its initial 10% market share with an added 1% every year. In the technical study and organizational study, technological alternatives regarding the manufacturing process, storage and transport were evaluated. Material requirements were based on the demand while equipment requirements were based on the design of the original proponents of coconut diesel. From here, a capacity plan was made. The capacity plan and schedule was determined to be five working days a week with two-day overtime. Premium Diesel, Inc. starts with 21 employees, six of which are contractual workers. Facilities plan, potential sites were assessed. The site will be located in Pasig, near its suppliers of diesel and CME. This plant is a rent-to-own facility where maximum efficiency can be achieved at the lowest possible rental cost. The technical feasibility was finally concluded when, after performing cost analysis, it was established that operating a mixing plant for coconut diesel is profitable. The project cost that will make this venture operational is estimated to be P10,107,881.85. These will be used for the acquisition of fix investments such as the site and equipment, to subsidize the pre-operating cost and cost of working capital such as raw materials, overhead costs and salary of the employees. This can be easily funded through equity financing. All stocks will be sold at the beginning of the year at the amount of P100 per stock. The suppliers are encouraged and expected to be among the investors. This way, the cost of raw materials may be reduced. With this set-up, the project will continually have an average net income of P3,647,766.91 and average ending cash balance of P9,392,302.67 every year. Its IRR is 21.6894%, which is greater than the MARR=15% indicating the good financial position of the project. The payback period is three and a half years. A socioeconomic analysis was done to determine the social desirability of the project benefits included the jobs generated, the utilization of local business and payment of taxes. The qualitative benefits of the project were enumerated such as its contribution to the environment by minimizing the risk of pollution-related health problems and the utilization of vacant warehouses. However, the disbenefits of the project were the problem of waste disposal and fix salary of the employees. The project benefits and costs to the society and economy were quantified and the cost benefit ratio was computed. A ratio of 1.1565 was gotten indicating that the project has positive impact on the society. From the analyses done, it can be conducted that the manufacture of coconut diesel for commercial use is feasible and that establishing Premium Diesel, Inc. (PDI) as its first manufacturer is profitable, not only for the PDI itself, but also for the national and local communities.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Premium Diesel, Inc; Coconut oil as fuel; Coconut oil--Philippines.; Diesel fuels--Philippines.; Participatory monitoring and evaluation (Project management)